E6AP is essential for the proliferation of HPV-positive cancer cells by preventing senescence. - Alicia Avenhaus; Milica Velimirović; Julia Bulkescher; Martin Scheffner; Felix Hoppe-Seyler; Karin Hoppe-Seyler (PLoS Pathogens)
Oncogenic types of human papillomaviruses (HPVs) are major human carcinogens. The formation of a trimeric complex between the HPV E6 oncoprotein, the cellular ubiquitin ligase E6AP and the p53 tumor suppressor protein leads to proteolytic p53 degradation and plays a central role for HPV-induced cell transformation. We here uncover that E6AP silencing in HPV-positive cancer cells ultimately leads to efficient induction of cellular senescence, revealing that E6AP acts as a potent anti-senescent factor in these cells. Thus, although the downregulation of either E6 or E6AP expression also acts partially pro-apoptotic, HPV-positive cancer cells surviving E6 repression proliferate further, whereas they become irreversibly growth-arrested upon E6AP repression. We moreover show that the senescence induction following E6AP downregulation is mechanistically highly dependent on induction of the p53/p21 axis, other than the known pro-senescent response of HPV-positive cancer cells following combined downregulation of the viral E6 and E7 oncoproteins. Of further note, repression of E6AP allows senescence induction in the presence of the anti-senescent HPV E7 protein. Yet, despite these mechanistic differences, the pathways underlying the pro-senescent effects of E6AP or E6/E7 repression ultimately converge by being both dependent on the cellular pocket proteins pRb and p130. Taken together, our results uncover a hitherto unrecognized and potent anti-senescent function of the E6AP protein in HPV-positive cancer cells, which is essential for their sustained proliferation. Our results further indicate that interfering with E6AP expression or function could result in therapeutically desired effects in HPV-positive cancer cells by efficiently inducing an irreversible growth arrest. Since the critical role of the E6/E6AP/p53 complex for viral transformation is conserved between different oncogenic HPV types, this approach could provide a therapeutic strategy, which is not HPV type-specific.